Physiopathology of Bone Modifications in β-Thalassemia - Carlo Perisano; Emanuele Marzetti; Maria Silvia Spinelli; Cinzia Anna Maria Callà; Calogero Graci; Giulio Maccauro (Anemia)
β-thalassemia major (βTM) or Cooley anemia is characterized by significantly reduced or absent synthesis of β-globin chains, which induces important pathologic consequences including hemolytic anemia, altered erythropoiesis, and bone marrow overstimulation. The pathogenesis of bone changes in patients with βTM is not yet completely understood. However, an unbalance in bone mineral turnover resulting from increased resorption and suppression of osteoblast activity has been detected in βTM patients. The abnormal regulation of bone metabolism may be related to hormonal and genetic factors, iron overload and iron chelation therapy, nutritional deficits, and decreased levels of physical activity. Here, we review the most recent findings on the physiopathology of bone abnormalities in βTM. Clinical presentation and radiological features of βTM-related bone changes are also discussed.